Formulation of Serum Sunflower (Helianthus annuus L.) Seed Oil as Antiacne Preparation - Soraya Ratnawulan Mita Mita; Sri Agung Fitri Kusuma; Devani Olivia Winardi; Patihul Husni; Yoshihito Shiono (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
Acne is caused by a microbial imbalance due to the overgrowth of Propionibacterium acnes in the skin microbiome. Sunflower seed oil (Helianthus annuus L.), which contains linoleic acid and terpenoids, has an antibacterial activity against P. acnes. This study aimed to increase the availability of anti-acne compounds from natural resources by formulating an anti-acne serum containing sunflower seed oil. The research methods included antibacterial activity testing of sunflower seed oil, serum formulation, product evaluation, and serum effectiveness testing. The results of the antibacterial activity test of sunflower seed oil against P. acnes ATCC 6919 showed a minimum inhibitory concentration (MIC) of 100 mg/mL and a minimum bactericidal concentration (MBC) of 200 mg/mL. The result of serum evaluation and stability testing during the freeze-thaw cycling test depicted stable formulation for all formulas based on organoleptic parameters, homogeneity, pH, viscosity, and spreadability. The effectiveness test results of the serum preparation showed that formula 3, containing 200 mg/L of sunflower seed oil, was the best formula with an inhibition zone diameter of 12.76 ± 0.03 mm. In conclusion, sunflower seed oil demonstrates the ability to prevent and treat acne-prone skin, making it a suitable alternative anti-acne compound.